Indole Propionic Acid, an Unusual Antibiotic Produced by the Gut Microbiota, With Anti-inflammatory and Antioxidant Properties - Negatu, Dereje Abate; Gengenbacher, Martin; Dartois, Véronique; Dick, Thomas (Frontiers in Microbiology, 2020)
Most antibiotics are produced by soil microbes and typically interfere with macromolecular synthesis processes as their antibacterial mechanism of action. These natural products are often large and suffer from poor chemical tractability. Here, we discuss discovery, mechanism of action and the therapeutic potentials of an unusual antibiotic, indole propionic acid (IPA). IPA is produced by the human gut microbiota. The molecule is small, chemically tractable, and targets amino acid biosynthesis. IPA is active against a broad spectrum of mycobacteria, including drug resistant Mycobacterium tuberculosis and non-tuberculous mycobacteria. Interestingly, the microbiota-produced metabolite is detectable in the serum of healthy individuals, tuberculosis (TB) patients, and several animal models. Thus, the microbiota in our gut may influence susceptibility to mycobacterial diseases. If a gut–lung microbiome axis can be demonstrated, IPA may have potential as a biomarker of disease progression, and development of microbiota-based therapies could be explored. In addition to its antimycobacterial activity, the molecule displays anti-inflammatory and antioxidant properties. This raises the possibility that IPA has therapeutic potential as both antibiotic and add-on host-directed drug for the treatment of TB in patient populations where disease morbidity and mortality is driven by excessive inflammation and tissue damage, such as TB-associated immune reconstitution inflammatory syndrome, TB-meningitis and TB-diabetes.